2023
DOI: 10.1097/md.0000000000032663
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasound-guided acupotomy for knee osteoarthritis: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background: This systematic review aimed to evaluate the effectiveness and safety of ultrasound-guided acupotomy (UGAT) therapy in the treatment of patients with knee osteoarthritis (KOA). Methods: We conducted online researches in the databases including PubMed, the Cochrane Library, EMBASE, China national knowledge infrastructure, China biomedical literature database, and Wan Fang data. All data were collected until January 1, 2022. Relevant randomized controlled trials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, studies on ultrasound guide procedures have been reported to increase the accurate depth of the needle and the accuracy of the treatment area. 25,26 It is thought that further research is needed on this method. Adverse effects in relation to either acupotomy alone or combination treatment did not occur, and there were no significant differences in…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on ultrasound guide procedures have been reported to increase the accurate depth of the needle and the accuracy of the treatment area. 25,26 It is thought that further research is needed on this method. Adverse effects in relation to either acupotomy alone or combination treatment did not occur, and there were no significant differences in…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, many respondents reported local AEs such as pain, bruising, hematomas, and bleeding due to vascular damage. However, the subgroup analysis indicated that these side effects can be minimized when utilizing medical imaging devices actively during procedures, highlighting the importance of their active utilization [ 30 ]. Regarding systemic AEs, fatigue and autonomic nervous system dysfunctions (headache, nausea, dizziness, sweating, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The needling depth may vary depending on gender, body mass index, and treatment area. The absence of navigational imaging devices may cause serious AEs [ 14 , 15 , 30 ]. Therefore, it is necessary to provide guidelines for safety procedures, including potential AEs based on individual patient characteristics, and procedural guidelines utilizing medical imaging devices, including safe needling depths [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, ultrasound-guided acupotomy was more effective in reducing pain than unguided acupotomy for patients with knee osteoarthritis in several randomized controlled trials. [8] In Korea, several retrospective studies reported positive effects of ultrasoundguided pharmacopuncture for the treatment of various musculoskeletal disorders, such as rib fracture and acute lower back pain. [9][10][11][12][13][14][15] Through these reports, it can be inferred that ultrasoundguidance is actively applied in the clinical practice of KM.…”
Section: Introductionmentioning
confidence: 99%